Croatian traditional songs from Međimurje on the trace of Havelock's cognitive-linguistic concepts - Bajuk, Lidija (Anafora, 2022)
This paper attempts to classify the Croatian traditional songs from Međimurje according to two basic cognitive-linguistic concepts, presented in 1986 in The Muse Learns to Write: Reflections on Orality and Literacy from Antiquity to the Present by American philologist Eric Alfred Havelock. The two categories of traditional songs are: songs passed on by oral tradition, which present the behavior of mythical beings and people in mythical natural or real cultural settings (A), and songs passed on by written word which articulate the "myself" (B). Cognitive linguistics as a contemporary humanistic discipline considers in context the two-way creative correlation between the worldview of the author-performer and the listener – whose personal views reinterpret and redefine the world.